Faktor-Faktor yang Mempengaruhi Penerimaan Mahasiswa Terhadap E-Learning Exelsa Moodle dengan Menggunakan Getamel - Nicolas Bayu Kristiawan (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2021)
The purpose of this study was to test student acceptance of Exelsa Moodle's e-learning using the General Extended Technology Acceptance Model for e-learning (GETAMEL) developed by Fazil and Rupert. The GETAMEL model is used with the aim of knowing specifically the factors that influence student acceptance of Exelsa Moodle e-learning. Based on GETAMEL, there are five external factors that influence student acceptance of e-learning, namely: experience in using computers and information technology, subjective norms, perceived comfort in using computers and information technology, anxiety in using computers and information technology, and self-efficacy. Survey research method is used to measure variables in GETAMEL. The results in this study indicate that not all external variables in GETAMEL affect the perception of convenience and the perception of usefulness in TAM. Only 2 variables have an effect, namely: the convenience variable in using e-learning, only affects the perception of ease in using Exelsa Moodle e-learning while the self-efficacy variable affects the perception of ease in using Exelsa Moodle e-learning and the perceived usefulness in using e-learning Excel Moodle. Furthermore, all variables in TAM have a significant effect